Primary health care pharmacists and vision for community pharmacy and pharmacists in Chile - Francisco Martinez-Mardones; Antonio Ahumada-Canale; Loreto Gonzalez-Machuca; Jose C. Plaza-Plaza (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
The Chilean healthcare system is composed of public and private sectors, with most of the higher-income population being covered privately. Primary healthcare in the public system is provided in more than 2,500 public primary care centers of different sizes with assigned populations within territories. Private insurance companies have their own healthcare networks or buy services from individual health providers. Patients from the public system receive most medications free of charge in primary care pharmacies embedded in each care center. Private patients must purchase their medicines from community pharmacies. Some government policies subsidize part of the cost of medications, but original medicines remain as the most expensive of Latin America. Three chain pharmacies have more than 90% of the market share, and these pharmacies have negative public perception because of price collusion court sentences. A non-profit, municipal pharmacy model was developed but has limited implementation. Most privately owned independent and chain community pharmacies do not provide pharmaceutical services as there is no remuneration or cover by insurers. The limited number of publicly owned Municipal pharmacies could implement pharmaceutical services in community settings as they are non-profit establishments and have full-time pharmacists but are not resourced for these services. A limited number of pharmaceutical services are almost exclusively provided in public primary care, including medication reviews, pharmaceutical education, home visits and pharmacovigilance services, but several barriers to their implementation remain. A risk-based multimorbidity care model was implemented in 2020 for public primary care with additional employment of part-time pharmacists to provide services. We believe that this model will help pharmacists to optimize their time by prioritizing the much-needed clinical tasks. We propose within this multimorbidity care model that the more time-consuming services are provided to higher risk patients. Pharmacy prescribing i.e. amending or approving changes in medications in primary care for chronic conditions could also be useful for the health system, but pharmacists would require additional training. The landscape for pharmaceutical services for primary care in Chile is promising, but the integration with community pharmacies will not be possible until they are funded by public and private insurance, and the public perception of these establishments is improved.